Does Size Matter? The Impact of Changes in Household Structure on Income Distribution in Germany - Andreas Peichl; Nico Pestel; Hilmar Schneider (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
In Germany, two observations can be made over the past 20 years: First, income inequality has been constantly increasing while, second, the average household size has been declining dramatically. The analysis of income distribution relies on equivalence-weighted incomes which take into account household size. Therefore, there is an obvious link between these two developments. The aim of the paper is to quantify how the trend towards smaller households has influenced the change in income distribution. In order to do so, we are using a decomposition of changes in inequality measures over time allowing for a separation between wage and demographic effects respectively. We propose similar decompositions for the change in poverty and richness as well and compare them with results that were obtained by a re-weighting procedure. Our results show that the income gap would also have increased without the demographic trend. But its level would be lower than it actually is. In addition, the demographic effect turns out to be larger for incomes before tax and benefits.
Keywords: D31; D63; J11; 330; income distribution; demography; household size; decomposition; Germany; Einkommensverteilung; Haushaltseinkommen; Privater Haushalt; Familiensoziologie; Deutschland